2021
DOI: 10.1177/09564624211040951
|View full text |Cite
|
Sign up to set email alerts
|

A survey of condom use among female sex workers in Northern Sydney; declining condom use for fellatio

Abstract: Condom use among female sex workers (FSWs) is dynamic. We conducted a survey, by anonymous questionnaire, of condom use among FSWs routinely attending our clinical service in Northern Sydney. Logistic regression models determined associations with inconsistent condom use. All 201 women approached completed a questionnaire. Chinese-born women comprised 67% of participants. The median age was 35 years. Clients requesting unprotected fellatio was reported by 95% of participants, and approximately two-thirds felt … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…The rising infection rates described here, particularly among FSWs born in China, agree with reports of lower condom use for oral sex among FSWs in Australia, 10,12,13,20 and the influence of monetary pressure from clients for unprotected oral and vaginal sex. 10 While dedicated outreach and clinical services have been effective so far in protecting the sexual health of FSWs in Australia, additional mechanisms are needed to address the financial pressure for condomless sex.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The rising infection rates described here, particularly among FSWs born in China, agree with reports of lower condom use for oral sex among FSWs in Australia, 10,12,13,20 and the influence of monetary pressure from clients for unprotected oral and vaginal sex. 10 While dedicated outreach and clinical services have been effective so far in protecting the sexual health of FSWs in Australia, additional mechanisms are needed to address the financial pressure for condomless sex.…”
Section: Discussionsupporting
confidence: 87%
“…9 A recent survey of condom use among FSWs at our service found only 26% used condoms consistently for fellatio, while 76% used condoms consistently for vaginal sex, and that FSWs born in China were less likely to use condoms due to financial incentives from clients. 10 Several other surveys have found a similar trend. [11][12][13] A recent national study among FSWs in Australia reported a rising incidence of chlamydia and gonorrhoea, particularly pharyngeal.…”
Section: Introductionmentioning
confidence: 52%
“…Other contributors could include a diminished ability of older sex workers to negotiate condom use with clients, heightening their vulnerability to HIV. Older FSWs might encounter more challenges in enforcing condom use, particularly when compared to their younger counterparts ( 33 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…(Tomko et al 2019), to which participants replied using a 5-category Likert scale: never, almost never, occasionally, almost every day, every day. The decision to not include condomless oral sex was made on the basis of it being a widespread practice (Lee et al 2021) and having a low risk of associated HIV infection ("HIV/AIDS" n.d.).…”
Section: Study Outcomes (Dependent Variables)mentioning
confidence: 99%